(untitled) (Global Journal of Human-Social Science, 2019)
Unlike financial services in developed countries, it is necessary to investigate the outreach of financial services in developing countries such as Tanzania. The study investigated the determinants of financial exclusion using data from Fin scope collected from April to July 2017 with a sample of 9,459 adults’ aged 16 years and above. The study adopted a multinomial logistic regression for Savings and borrowing models. Through borrowing model, gender, marital status, education, wealth index, access to mobile phone, financial education, payments of utility bills, location and individual income are statistically significant influencing borrowing. The results from saving model reveal that age, gender, marital status, education, wealth index, access to mobile phone, employed, financial education, utility payment bills, household size, location, and individual income are the critical factor for saving among adults. Finally, the study recommends that the government through its respective organs promote and facilitate the investment of financial institutions to the investors who can develop and establish financial services, which are sensitive to young people, and women who are poor. Cell phones are basic infrastructures for financial deepening; banks, microfinance, non-bank payment service, and mobile money service providers should use them at the level whereevery group in the society such as poor people can access and use financial services.Provision of financial education in remote rural still vital to creating awareness on the importance of financial service on economic activities thereby attaining inclusive economic growth.